Terapia ocupacional e conceito neuroevolutivo Bobath na reabilitação da pessoa com AVE - MODESTO, Deyse Pantoja (2023)
INTRODUCTION: Stroke is defined by the World Health Organization (WHO) as an acute neurological dysfunction of vascular origin that results in cognitive and sensorimotor changes. Survivors after stroke usually have difficulties in performing activities of daily living. Thus, Occupational Therapy (TO) contributes to the rehabilitation of patients after stroke, since its main objective is to enable the autonomy and independence of the subject in their daily lives. Among the strategies that can be used by the occupational therapist is the Bobath neuroevolutionary concept, which encourages the reacquisition of more functional movement patterns. OBJECTIVE: To evaluate the effects of Bobath neuroevolutionary therapy on the occupational therapeutic treatment of patients with stroke sequelae. METHODOLOGY: This is a qualitative and quantitative longitudinal case study, conducted with two male patients. The consultations took place from September to December 2018, at the Federal University of Pará. The patients participated in the initial evaluation, then 10 therapy sessions (twice a week, one hour per session), and were reassessed for the first time. . Next 10 more sessions and then the second reevaluation. The protocols used in the evaluation were: Mini Mental State Examination (MMSE); Canadian Occupational Performance Measure (COPM); Wolf Motor Function Test (WMFT) and the Fugl Meyer Scale (EFM). RESULTS AND DISCUSSION: With regard to COPM, patients showed improvement in performance and satisfaction in almost all activities. All calls involved occupations as a resource and / or purpose. In addition, several principles (motivation, transference, intensity, repetition) and techniques (tapping, placing, holding) related to the Bobath concept were contemplated in the consultations. In WMFT, there was a decrease in the average execution time for P1 and an increase for P2. As for functional ability, there was an increase in the score for P1 and maintenance of the score for P2. In Fugl Meyer, P1 had a 23.86% increase in the total score, and P2 had a 6.58% increase in the total score. CONCLUSION: Occupational Therapy and the Bobath Concept are significant in the post-stroke patient rehabilitation process. A limitation of this study is the number of patients, and further research with a larger number of patients is required.